Perceived Usefulness Of Generative AI dan Ethical AI Use Intention: Peran Mediasi Academic Integrity Awareness Di Perguruan Tinggi - Gracela Marisa Sanapang; Moh Virgiawan Antralis; Muh Dafa Wardana; Yusri Hidayat; Nur Ichsan; Rahmat Mursalim (Movere Journal, 2026)
The rapid diffusion of generative artificial intelligence (GenAI), such as ChatGPT, has reshaped students’ academic practices, primarily due to its perceived ability to enhance efficiency and learning productivity. Nevertheless, high perceived usefulness may also increase the risk of unethical academic use when students lack adequate awareness of academic integrity. Grounded in the Technology Acceptance Model (TAM) and an intention-based perspective, this study examines the effect of perceived usefulness of generative AI on students’ ethical AI use intention, with academic integrity awareness positioned as a mediating mechanism. A quantitative explanatory design was employed using an online survey targeting higher-education students who have used GenAI for academic purposes. Respondents were selected via purposive sampling. Data were collected through a five-point Likert-scale questionnaire and analyzed using SEM-PLS (SmartPLS), applying bootstrapping to test direct effects and mediation simultaneously. The results indicate that perceived usefulness positively and significantly predicts academic integrity awareness and ethical AI use intention. Academic integrity awareness also has a positive and significant effect on ethical AI use intention. Indirect-effect testing confirms a significant mediating role of academic integrity awareness in the relationship between perceived usefulness and ethical AI use intention, suggesting partial mediation. These findings imply that ethical GenAI use is not driven by perceived usefulness alone; it also depends on students’ internalized academic integrity awareness. Practically, higher-education institutions should strengthen ethical literacy, institutional policies, and governance frameworks for GenAI to ensure effective yet responsible adoption.